Analyzing the adhesion mechanism of FnBPA, a surface adhesin from Staphylococcus aureus on its interaction with nanoparticle. (September 2020) - Ponnuvel, Shobana; Sankar, Sreejanani; Ponnuraj, Karthe
Abstract: Staphylococcus aureus expresses many Microbial Surface Recognizing Adhesive Matrix Molecules (MSCRAMM's) to recognize host extracellular matrix (ECM) molecules to initiate colonization. The MSCRAMM, fibronectin binding protein A (FnBPA), is an important adhesin for S. aureus infection. FnBPA also binds with fibrinogen (Fg) by using a unique ligand binding mechanism called dock, lock and latch. Nanoparticles, especially nanosilver particles have been widely used in a variety of biomedical applications which includes disease diagnosis and treatment, drug delivery and implanted medical device coating. In a biological system, when protein molecules encounter nanoparticle, they can be absorbed onto its surface which results in the formation of protein corona. In the present study, we have analysed the fibrinogen binding ability of rFnBPA(189-512) in the presence of silver nanoparticles by employing techniques like gel shift assay, Western blot, size exclusion chromatography, enzyme-linked immunosorbent assay, bio-layer interferometry and circular dichroism spectroscopy. The results indicate that rFnBPA(189-512) is unable to bind to Fg in the presence of a nanoparticle. This could be due to the inaccessibility of the Fg binding site and conformational change in rFnBPA(189-512) . With nanoparticles, rFnBPA(189-512) undergoes significant structural changes as the β-sheet content has drastically reduced to 10% from the initial 60% at higher concentration of the nanoparticle. Pathogenic bacteria interact with its surrounding environment through their surface molecules which includes MSCRAMMs. Therefore MSCRAMMs play an important role when bacteria encounter nanoparticles. The results of the present study suggest that the orientation of the protein during the absorption on the surface of a nanoparticle as well as the concentration of the nanoparticle, will dictate the function of the absorbed protein and in this case the Fg binding property of rFnBPA(189-512) . Highlights: FnBPA is a critical adhesin implicated in S. aureus infections. rFnBPA(189-512) was cloned, expressed and purified to near homogeneity. Fibrinogen affinity of rFnBPA(189-512) was analysed in the presence of silver nanoparticles. Nanoparticles impairs the fibrinogen binding dock, lock and latch mechanism of rFnBPA(189-512) .